Bickerstaff's Genuine Boston Almanack, or, Federal Calendar, for 1791. Third after Leap-Year; and Fifteenth of Independency. (Tufts University. Tisch Library., 2018)
12 leaves. Tisch Library copy contains handwritten annotations. Essay and narrative content includes: A curious, historical and entertaining Narrative of the Captivity and almost unheard-of Sufferings and cruel Treatment of Mr. Robert White, Mariner.